A handbook of journalism :media in the information age - Anand, V. Eshwar,Ed; Jayanthi, K,Ed (Sage, 2018)
Journalism as a discipline is becoming increasingly important today. It has to contend with new challenges such as the explosion of social media, heightened commercial competition in the mainstream media and the emergence of the media as a powerful actor in public policy and governance. The confluence of these factors calls for fresh thinking about the teaching and practice of journalism.